Exercise-mobilized donor lymphocyte infusions enhanced with cytokine stimulation for the prevention and treatment of leukemic relapse after allogeneic hematopoietic cell transplantation - McDougal, London M.; Baker, Forrest L.; Gustafson, Michael P.; Katsanis, Emmanuel; Simpson, Richard J. (Frontiers in Immunology, 2025)
Donor lymphocyte infusions (DLI) are a standard therapy following allogeneic hematopoietic cell transplantation (alloHCT) for preventing and treating leukemic relapse in high-risk patients, particularly those with myeloid malignancies such as acute myeloid leukemia (AML), chronic myeloid leukemia (CML), and myelodysplastic syndrome (MDS). However, the efficacy of DLI remains suboptimal and is accompanied by a significant risk of life-threatening graft-versus-host disease (GvHD), highlighting the urgent need for strategies that enhance graft-versus-leukemia (GvL) effects while mitigating GvHD. We propose that engaging donors in an acute bout of exercise during peripheral blood lymphocyte collection represents a promising strategy to enhance GvL activity whilst mitigating the risk of GvHD. A single bout of cardiorespiratory exercise triggers catecholamine- and β2-adrenergic receptor-dependent mobilization of effector lymphocytes into the bloodstream, significantly increasing the proportion of GvL-promoting NK-cells and γδ T-cells relative to total CD3+ T-cells while reducing GvHD-promoting naïve CD4+ and CD8+ T-cells. Preclinical evidence suggests that these exercise-mobilized lymphocytes infiltrate tumors, exhibit enhanced leukemic control in xenogeneic mice, and display transcriptomic and proteomic profiles indicative of heightened anti-tumor immunity, migration potential and cytokine responsiveness. In this narrative review, we evaluate the advantages and limitations of DLI as a post-alloHCT therapy and propose the novel concept of exercise-enhanced donor lymphocyte infusions (DLI-X) as a simple and cost-effective strategy to augment GvL effects in preventing and treating leukemic relapse. Additionally, we propose that enriching DLI-X with NK-cell-enhancing cytokines (e.g., IL-12, IL-15, and IL-18) will create a novel therapeutic product, termed DLI-XS, with enhanced potency for post-alloHCT applications. We also discuss how DLI-X and DLI-XS, can be leveraged in combination with other post-transplant interventions to maximize GvL effects while minimizing GvHD risks. Finally, we explore the critical role of donor fitness (e.g. V̇O2max) in potentially influencing clinical outcomes of alloHCT and post-transplant cell therapies. This comprehensive integration of DLI-X and DLI-XS into existing treatment paradigms represents a promising avenue for enhancing therapeutic outcomes in leukemic relapse post-alloHCT and will underscore the transformative potential of exercise as an accessible and cost-effective adjuvant for DLI.